The expression of CD25, CD11b, SWC1, SWC7, MHC-II, and family of CD45 molecules can be used to characterize different stages of γδ T lymphocytes in pigs - Stěpánová, Kateřina; Sinkora, Marek (Developmental and comparative immunology, 2012)
The expression of selected molecules was chosen to study porcine γδ lymphocytes and their CD2/CD8 subsets in different lymphoid organs in vivo and in vitro. Results indicate that many γδ T cells can constitutively express CD25 and MHC-II and that the frequency of γδ T cells positive for CD25, CD11b, SWC1 and SWC7 can be increased by stimulation. A diversified TCRδ repertoire was found inside CD25(+), CD11b(+), SWC1(-) and CD45RA(-) cells. Ontogenetic studies revealed various age and/or colonization dependency for expression of all studied molecules except of SWC7. Findings generally indicate that CD25 represent an activation molecule that probably marks a functionally distinct subsets, expression of CD11b is perhaps connected to early functions of naive γδ T cells in the periphery, SWC1 is lineage specific marker, SWC7 may represent an activation molecule with intrinsic or transient expression, and the expression of CD45RA/RC most likely defines naive and terminally differentiated cells.
Keywords: T-lymfocyty - podskupiny; Swine; Interleukin-2 Receptor alpha Subunit; prasata; Leukocyte Common Antigens; receptor interleukinu-2 - alfa-podjednotka; T-Lymphocyte Subsets; zvířata; Antigens, CD; antigeny CD45; CD antigeny; Animals